Ergonomic Design of Products and Worksystems - 21st Century Perspectives of Asia (Managing the Asian Century,, 2018)
This edited volume focuses on research conducted in the area of ergonomic design. Chapters are extensions of works presented at the International Conference on Management of Ergonomic Design, Industrial Safety and Healthcare Systems. The book addresses the need to have the knowledge of ergonomics, human factors engineering and safety engineering in order to make worksystems ergonomically designed, operationally safe and productive. It is a useful resource for students, researchers, industrial professionals, and design engineers.